The Use of Novel toTeach English Culture - Setyoningsih, Setyoningsih (Institut Agama Islam Negeri Kudus, 2018)
Learning language is considered as learning its culture since language is part of culture. This article talks about the use of novel as one of literature to learn culture of other countries. The object of the study is a novel Not Without my Daughter (NW) by William Hoffer and Betty Mahmoody which is based on the true story of Betty Mahmoody, an American woman who was trapped in Iran society with her daughter. This novel is chosen because it reflects the social and cultural conditions of people, who come into contact with other cultures. The analysis was carried out through the following process i.e. (1) categorizing the data; (2) interpreting the data; (3) drawing conclusion. The result shows that cultural conflicts occurred because of friction of different cultures between Betty’s cultures, in this case America, and Iran culture. The cultural aspects causing conflicts found in NW were belief, custom and habit, uses of time, law, dress and body language. By analyzing cultural conflict in the novel, students can get a better understanding of other cultures and increase their cultural awareness.